Présence de Bouvard et Pécuchet chez Roland Barthes - Anne Herschberg Pierrot (Flaubert: Revue Critique et Génétique)
The article emphasizes the constant presence of Bouvard et Pécuchet in Roland Barthes. It follows its development and pervasion in Barthes’ writing and lectures. The symbol of modernity in literature, Flaubert’s novel appears at once to be a critical encyclopedia of languages and an experimental model for writing, becoming for Barthes a major element in his thoughts about his own writing and about stupidity.